Novel Methacrylamide Polymers Based on Thiazole and Styrene: A Study on Synthesis, Characterization, and Determination of Monomer Reactivity Ratios - Soykan, Cengiz; Ergül, Ece (Journal of Research Updates in Polymer Science, 2022)
In this study, firstly, a thiazole methacrylamide (TMAAm) monomer was synthesized from methacryloyl chloride with 2-aminothiazole. Later on, a series of copolymers of 2-thiazole methacrylamide (TMAAm) with styrene (St) using strange compositions in the feed has been prepared in solution via radical at 70 oC with AIBN as initiator. The structure of the copolymers was elucidated by FT-IR, 1H-NMR, and 13C-NMR spectroscopy methods. The compositions of the copolymers were determined from the nitrogen (N) difference according to the elemental analysis results. Monomer reactivity ratios; The rTMAAm and rSt, Fineman-Ross (FR), Kelen-Tüdös (KT) linear methods, and the error method model in non-linear variables were calculated with the computer program RREVM. The molecular weights and heterogeneity indices of the copolymers were determined by the GPC method. The thermal stability of the copolymers was investigated by thermogravimetry (TG) measurements.